Evaluation of metal concentrations in Red Tilapia (Oreochromis spp) from three sampling sites in Jelebu, Malaysia using principal component analysis - Low, K.H.; Abas, M.R.; Zain, Sharifuddin Md (2011)
Concentration of V, Mn, Fe, Co, Cu, Zn, As, Se, Cd, and Pb in muscle, liver, and gill tissues of red tilapia (Oreochromis spp) sampled from three different aquaculture sites which include earthen pond, ex-tin mining pool, and concrete tank in Jelebu, Negeri Sembilan, were determined using microwave-assisted digestion-inductively coupled plasma-mass spectrometry. Accumulation patterns relating organs and elements, as well as origins and elements, were evaluated using multivariate statistics. With the aid of principal component analysis, it is possible to visualize the distribution pattern of metals in different organs as well as clustering tendencies of tilapia samples according to the production sites. In general, levels of V, Co, Fe, Cu, Zn, Se, and Cd in liver were higher than those in muscles and gills, whereas Mn and Pb were higher in gills while As in muscles. Results from principal component analysis revealed that there are similar pattern of metal distribution among organs regardless of the production sites. It is also suggested that Cu, As, and Pb are the best describers in characterizing the studied organs, where liver tissues are associated with high Cu, gills with high Pb, and muscles with high As. On the other hand, V, Co, and Pb are observed to be key discriminants for sample origins. © 2010 Springer Science+Business Media, LLC.